Frontmatter - The Editors (Classica et Mediaevalia, 2026)
Frontmatter. Tales from A Thousand Cities. Studies in Memory of Mogens Herman Hansen. Edited by Thomas Heine Nielsen, Lene Rubinstein, and Adam Schwartz.